Geostatistical Mapping of Folded Itabiritic Rocks of the Bonito Mine, Northeastern Brazil - Fonteles, Helano; Veríssimo, César Ulisses (Anuário do Instituto de Geociências, 2022)
Geological modeling is the primary task of any exploratory geological investigation, and it is performed even during the mine development. In the study area, the Serra dos Quintos Formation hosts banded iron formations represented by assorted itabirites. The database used in this work was exploited from a geological databank which was structured to gather data and information depicted from an exhaustive exploratory drilling program. A survey was performed throughout the entire databank to collect the available thickness data values (measured in meters) from drill core logs that intersected the itabirite. Since structural heterogeneities can occur within these rocks, this study aims to identify such features. Geostatistical estimation and simulation methods were employed to map folded itabiritic beds based on thickness data accurately. Kriging estimators are often used for practical reasons; however, sometimes, the estimates can be smoothed and do not represent the entire original data range. Simulation algorithms can yield several stochastic images, but local accuracy cannot always be guaranteed. Simulated annealing was performed by adjusting the global statistics and preserving the local accuracy. We demonstrated that the banded iron formations’ thicker areas might correspond to the antiform fold as the dominant tectonic feature in the study area. Finally, we show that the simulated thickness map discloses the thicker mineralized spots. Meanwhile, the thinner ones may unveil intrinsic structural heterogeneities mainly observed at the limbs of the Bonito fold, where intensive deformation within the itabiritic layer was higher than expected. Concerning the mining issues, information obtained from the simulated thickness map could provide ancillary data to improve mining planning in the study area.